Ferroptosis as a Potential Cell Death Mechanism Against Cisplatin-Resistant Lung Cancer Cell Line - Morteza Golbashirzadeh; Hamid Reza Heidari; Mehdi Talebi; Ahmad Yari Khosroushahi (Advanced Pharmaceutical Bulletin, 2023)
Purpose: Drug resistance is a challenging issue in cancer chemotherapy. Cell death induction is one of the main strategies to overcome chemotherapy resistance. Notably, ferroptosis has been considered a critical cell death mechanism in recent years. Accordingly, in this study, the different cell death strategies focused on ferroptosis have been utilized to overcome cisplatin resistance in an in vitro lung cancer model. Methods: The physiological functions of Akt1 and GPX4, as critical targets for ferroptosis and apoptosis induction, were suppressed by siRNA or antagonistic agents in resistant A549 cells. Afterward, the interventions’ impacts on cell viability and reactive oxygen species (ROS) amount were analyzed by flow cytometry. Moreover, the alteration in the relevant gene and protein expression levels were quantified using Real-time PCR and western blot methods. Results: The result showed that the treatment with Akt1 siRNA reversed the cisplatin resistance in the A549 cell line through the induction of apoptosis. Likewise, the combination treatment of the GPX4 siRNA or FIN56 as ferroptosis inducers alongside cisplatin elevated ROS’s cellular level, reduced the cellular antioxidant genes level and increased the cisplatin cytotoxic effect. Conclusion: In conclusion, our study indicated that ferroptosis induction can be considered a promising cell death strategy in cisplatin-resistant cancer cells.